Evaluación de la gestión del Préstamo Bancario obtenido y su incidencia en la liquidez del negocio unipersonal dedicado a la comercialización de Maíz. En los periodos 2010 y 2011 - Huamán García, Gerardo (2013)
The research paper entitled "Evaluation of bank loan obtained management and its impact on the liquidity of the sole proprietorship dedicated to the marketing of maize, periods 2010 and 2011"; owned by Mr. Walter Oliveira Lozano commercial reason Corn Selva hereinafter developed in this research, it aims to provide a tool for assessing the investment made on debt as financial leverage. Also determine the investment made to obey the result and the percentages obtained from commercial operations net of expenses to cover bank charges as can be seen in the ratio of capacity to pay and to cover its obligations on a monthly basis since political overall growth in the early years does not show the desired profitability.